Les traits balkaniques du subjonctif roumain - Cychnerski, Tomasz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
This paper aims to determine the Balkan features of the Roumanian subjunctive mood. The Balkanism is defined here as a linguistic unit which is peculiar to languages of the southeastern Europe, but does not characterize any other Indo-European language. In comparison with the subjunctive mood in French (and in other Western Romance languages), the Roumanian subjunctive mood can be considered a Balkanism. The features which unite it to the subjunctive mood in Albanian and Modern Greek (its frequency, its predominant syntactic nature and its null semantic invariant) are favourable to such classification.
The Balkan Features of the Roumanian Subjunctive